EVALUATION OF THE EFFECTIVENESS OF SURGICAL CORRECTION IN PATIENTS WITH TYPE II DIABETES MELLITUS - Oktyabr Teshayev,; Alimbay Mavlyanev,; Bahodir Tavasharov, (The Bioscan, 2025)
Diabetes mellitus is now so common in the population that it is beginning to displace malnutrition and infectious diseases as the most significant factor in poor quality of life. Despite the availability of various methods for treating diabetes mellitus, it is not always possible to achieve glycemic stabilization, which worsens the prognosis of the disease. The modern approach to treating diabetes mellitus in the absence of effect from drug therapy includes surgical methods such as bariatric surgery. This direction has become especially relevant in many foreign countries due to its effectiveness. In our republic, we are also involved in the fight against diabetes using various types of bariatric surgery. These operations are carried out in many clinics in our Republic.